Examining the Impact of Socioeconomic Inequality and Targeted Interventions on Healthcare Disparities - Balougun, Irreti; Tunde, Ibrahim; Ronke, Omotola (ScieClouds Publishing, 2023)
Healthcare disparities remain a critical challenge in Nigeria, where socioeconomic inequality, geographic barriers, and limited healthcare infrastructure contribute to unequal access to healthcare services and suboptimal health outcomes. This study employed a quantitative research approach to examine the impact of targeted interventions on healthcare disparities across urban and rural regions of Nigeria. Using a cross-sectional survey design, data were collected from 500 respondents, selected through stratified random sampling, to ensure representation across different socioeconomic groups and geographic locations. Descriptive analysis revealed that 44% of respondents reported fair or poor health, with the majority citing long distances to healthcare facilities and economic limitations as primary barriers to access. Inferential analysis using Pearson correlation showed a significant negative relationship between income level and healthcare access (r = -0.58, p < 0.05). Multiple regression analysis further demonstrated that targeted interventions, such as increased healthcare funding and community-based health programs, significantly predicted improvements in healthcare utilization and health outcomes (β = 0.67, p < 0.01). The study also highlighted disparities in maternal and child health indicators, emphasizing the need for tailored policies to address these issues. By integrating successful strategies from other countries, this research offers practical recommendations for policymakers to improve healthcare equity in Nigeria. The findings contribute to the existing literature by addressing gaps related to the effectiveness of targeted interventions in mitigating healthcare disparities in developing contexts.